FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN BERAT BADAN LAHIR RENDAH (Studi di Kabupaten Wonosobo, Jawa Tengah) - Wahyu Rochadi; Zinatul Faizah (Jurnal Kesehatan Masyarakat Indonesia, 2005)
The study was conducted or correlated to identified some factors with Low Birth Weight. Such as characteristic of mother, sosial cultur, nutrition state, health stqte, ante natal care, haemoglobin" oni iocline urine. The study was carried out in Wonosobo General Hospital and its suruouncling area during the month of June to December 1995. The first phase of the study was to collect descriptive formation on the prevalence of low birth weight in Wonosobo, ancl the second phase was to find factors associated with the law birth weight cases. Thirty low birth weight cases were taken randomly and thirty normal birth weight cases were chosen as controls. The stutly revealed tkst there were 55 cases low birth weight or 37. I 6 94 out of deliveries in the hospital during the month of June untill Sep;e*iber I 995. The mean birth weight 2027'3 grams and birth length 48.3 cm. Nine percent of the mothers come fyom antsicle Vl/onosobo. There were no difference in the age, weight and height of the mothers, number of children ancl ntiscarriage, haemoglobine and iodine contekt in the urine of the mother. The same condition was also found in the ante nata! care, physical condition and food pattern of both groups. However, mothers who delivered low birth weight babies ever had "jamu" (traditional herb al drink).Keywards: low birth weight, social culture, nutrition state, antenatal care